2020
DOI: 10.3233/wor-203217
|View full text |Cite
|
Sign up to set email alerts
|

Let’s get back to work: Preventive biological cycle management of COVID-19 in the workplace

Abstract: BACKGROUND: The primary response to the coronavirus (COVID-19) pandemic has been to minimize social contact through lockdown measures. The closure of non-essential businesses to tackle the spread of the coronavirus has had negative consequences for the global economy, production, and employment. OBJECTIVE: To outline how known occupational health principles can be used for preventative management of the coronavirus in workplaces to support resumption of work. METHODS: A discussion of current knowledge of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“… Garzillo et al, (2020) and O'Neill (2020) also agree that assessing biological risks is a challenge. Jahangiri et al, (2020) corroborate that the management of the biological cycle can control the risk of coronavirus infection and provide a good strategy to support the return of employees to work, including to training for the use of personal protective equipment ( Gharibi et al, 2020 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
See 4 more Smart Citations
“… Garzillo et al, (2020) and O'Neill (2020) also agree that assessing biological risks is a challenge. Jahangiri et al, (2020) corroborate that the management of the biological cycle can control the risk of coronavirus infection and provide a good strategy to support the return of employees to work, including to training for the use of personal protective equipment ( Gharibi et al, 2020 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
“… Dufour et al, (2020) ; Gharibi et al, (2020) ; Gallardo et al, (2020) discussed the adoption of OHS in companies to face COVID-19, since the economic consequences of lockdowns generate intolerable and irretrievable damage, causing marketing and behavioral problems for employees. Jahangiri et al, (2020) added that closing of non-essential businesses to confront COVID-19 had negative consequences for the global economy, production, and employment. Michaels and Wagner (2020) found that American companies face a massive worker safety crisis, affecting operational productivity.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations